Stranded [large type] - Kava, Alex (Kava, Alex. Maggie O'Dell series., 2013)
Tired travelers and truckers have stopped at rest areas for decades, but one man's rest stop is another's hunting ground. For years the weary and the stranded have disappeared along highways. But these seemingly unconnected incidents are no coincidence, and a serial killer stalks the roads. When FBI special agent Maggie O'Dell and her partner, Tully, discover the remains of a young woman in a highway ditch, the one clue left behind is a map -- an invitation of sorts for Maggie to play a game between killer and investigators that will take Maggie and Tully on a frantic hunt crisscrossing the country to stop a madman before he kills again. As the body count rises and Maggie races against the clock to unmask the monster who's terrorizing the nation's highways, she turns to a former foe for help since he seems to know just what the killer's next move will be. As she gets closer to finding the killer, it becomes eerily clear that Maggie is the ultimate target.